2021
DOI: 10.2147/dmso.s320169
|View full text |Cite
|
Sign up to set email alerts
|

The Profile and Function of Gut Microbiota in Diabetic Nephropathy

Abstract: Introduction: Dysbiosis of gut microbiota impairs the homeostasis of immune and metabolic systems. Although previous studies have revealed the correlation between gut microbiota and various diseases, the function between gut microbiota and diabetic nephropathy (DN) has not been discovered distinctly. In this study, we tried to investigate the profile and function of gut microbiota in DN. Methods: A total of 100 people were enrolled in this study. Twenty were healthy people, 20 were diabetes patients, and 60 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 34 publications
2
45
1
Order By: Relevance
“…These changes coupled with increased levels of Akkermansia in the gut may contribute to the effects of metformin on glucose metabolism [ 22 ]. It appears that the metabolic factors associated with chronic low-grade inflammation and oxidative stress, which link gut microbiota dysbiosis and type 2 diabetes, are the same ones that influence the onset and progression of diabetic complications [ 23 , 24 ]. This relationship gives credence to the concept that modulation of the gut microbiota may be a promising strategy in the management of diabetes and associated complications as presented in the following sections.…”
Section: Gut Microbiota Type 2 Diabetes and Its Complicationsmentioning
confidence: 99%
“…These changes coupled with increased levels of Akkermansia in the gut may contribute to the effects of metformin on glucose metabolism [ 22 ]. It appears that the metabolic factors associated with chronic low-grade inflammation and oxidative stress, which link gut microbiota dysbiosis and type 2 diabetes, are the same ones that influence the onset and progression of diabetic complications [ 23 , 24 ]. This relationship gives credence to the concept that modulation of the gut microbiota may be a promising strategy in the management of diabetes and associated complications as presented in the following sections.…”
Section: Gut Microbiota Type 2 Diabetes and Its Complicationsmentioning
confidence: 99%
“…[179][180][181] Several studies have shown alterations in gut bacterial abundance in patients with diabetic nephropathy compared to controls, and overall lower bacterial diversity was correlated with disease progression. [182][183][184] In rodents, diabetic nephropathy was associated with altered bacterial communities and microbial metabolites like phenyl sulfate 185,186 and correlated with activation of the renin-angiotensin system. 187,188 Several observational studies have tested the effect of Ramadan fasting on diabetic nephropathy severity, but none of them showed significant changes in renal functions.…”
Section: Intermittent Fasting and Microbial Regulation In Long-term C...mentioning
confidence: 99%
“…In diabetic patients, poor glycemic control and hypertension can lead to glomerular hyperfiltration, albuminuria, nephrotic proteinuria, and development of end‐stage renal disease 179–181 . Several studies have shown alterations in gut bacterial abundance in patients with diabetic nephropathy compared to controls, and overall lower bacterial diversity was correlated with disease progression 182–184 . In rodents, diabetic nephropathy was associated with altered bacterial communities and microbial metabolites like phenyl sulfate 185,186 and correlated with activation of the renin‐angiotensin system 187,188 .…”
Section: Intermittent Fasting and Microbial Regulation In Long‐term C...mentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a common serious microvascular complication of diabetes mellitus (DM) and is associated with significantly increased morbidity and mortality [ 43 ]. Around one third of DM patients develop DN, which is a leading cause of end-stage renal disease (ESRD) [ 44 ]. Five stages (Stage I to V) of DN exist and are categorized based on glomerular filtration rate (GFR) and albuminuria [ 44 ].…”
Section: Dysbiosis and The Urothelial Systemmentioning
confidence: 99%
“…Around one third of DM patients develop DN, which is a leading cause of end-stage renal disease (ESRD) [ 44 ]. Five stages (Stage I to V) of DN exist and are categorized based on glomerular filtration rate (GFR) and albuminuria [ 44 ]. Most of the time, DN is diagnosed once patients have already progressed to stage III or IV, which is considered irreversible [ 45 ].…”
Section: Dysbiosis and The Urothelial Systemmentioning
confidence: 99%